Serum calprotectin correlates with severity of severe fever with thrombocytopenia syndrome - Cai, Shijie; Zhu, Jiahua; Xu, Zhiye; Chen, Wenqin; Tao, Yue; Huang, Taihong; Wang, Sen (Frontiers in Microbiology, 2025)
IntroductionSevere fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease caused by Dabie bandavirus (DBV), clinically characterized by fever, thrombocytopenia, and multiple organ dysfunction. Severe cases are often associated with cytokine storms and exhibit a high mortality rate. Calprotectin (CP), an inflammatory marker mainly expressed in neutrophils and monocytes, has been linked to disease activity and prognosis in various inflammatory conditions. This study aimed to investigate the changes in serum calprotectin (sCP) levels and their clinical relevance in SFTS patients.MethodsSerum calprotectin levels were measured in 60 patients diagnosed with SFTS and compared with those in 60 healthy controls. The association of sCP levels with disease severity, outcome, inflammatory markers, viral load, cytokines, and clinical parameters was analyzed.ResultssCP levels were significantly elevated in SFTS patients compared to healthy controls. Severe cases and non-survivors had notably higher sCP levels than mild cases and survivors, respectively. sCP levels showed positive correlations with viral load, inflammatory cytokines (e.g., TNF-α, IL-6, IL-8, IL-10), and clinical parameters such as CRP, AST, LDH, and D-dimer. Moreover, increased sCP levels were observed in patients with renal injury, hepatic injury, and neurological symptoms.DiscussionThe present study suggests that sCP levels are closely related to disease severity and prognosis, highlighting its potential as a biomarker for diagnosing and prognostic assessment in SFTS patients.